2019
DOI: 10.36348/jaep.2019.v03i11.003
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Strategic Plan in Influencing Academics in Public Teachers Colleges in Tanzania

Abstract: The study has examined the Influence of strategic planning in improving academics in public Diploma Teachers Colleges in Tanzania. The study used mixed research methods, under concurrent triangulation design. The purpose of using this design was to bring together the differing strengths and non-overlapping weaknesses of quantitative methods with those of qualitative methods. The sample sizes of 10 colleges out of 35 public teachers Colleges with 140 respondents out of the entire population were selected for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…A critical analysis of the above comment revealed that, adoption of strategic implementation practices in terms of teachers' involvement in the allocation and distribution of their roles, enhances their levels of motivation towards hard working which in turn influences students' academic performance. This finding supports the empirical work by Meigaru et al [20] who observed that, involvement of tutors in setting goals and operational activities made it easier to scale up and improve students' academic performance in public teacher colleges in Tanzania. Likewise, Kwaslema and Onyango [26] revealed that, strategic implementation practices in terms of teachers' involvement in determination of short-term plans and school activities contributed to enhanced motivation among the school community to work hard as a team and eventually improved students' performance [51].…”
Section: The Influence Of Strategic Implementation Practices On Stude...supporting
confidence: 89%
See 3 more Smart Citations
“…A critical analysis of the above comment revealed that, adoption of strategic implementation practices in terms of teachers' involvement in the allocation and distribution of their roles, enhances their levels of motivation towards hard working which in turn influences students' academic performance. This finding supports the empirical work by Meigaru et al [20] who observed that, involvement of tutors in setting goals and operational activities made it easier to scale up and improve students' academic performance in public teacher colleges in Tanzania. Likewise, Kwaslema and Onyango [26] revealed that, strategic implementation practices in terms of teachers' involvement in determination of short-term plans and school activities contributed to enhanced motivation among the school community to work hard as a team and eventually improved students' performance [51].…”
Section: The Influence Of Strategic Implementation Practices On Stude...supporting
confidence: 89%
“…Although much literature is available on the influence of strategic planning on organisational performance, only a few studies focused their attention on education sector organisations and public secondary schools in particular. Besides, the available studies such as Meigaru et al [20] and Kwaslema and Onyango [26] assessed the variable school performance in a narrow definition based only on students' achievement indicators. Hence, little evidence is available on the relationship between strategic planning practices and school performance as a multilevel variable assessed at a school organisational level, teacher level and students' achievement level.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The SEM test found that the relationship between the implementation of the organizational strategic plan and the school's academic achievement was significant at a positive value. The study gave the same findings as Agi (2017); Al-Mawdieh (2020); Ameen (2019); Caputo and Rastelli (2014); Kasan (2013); Ebiziem et al (2021); Ford and Ihrke (2019); Kwaslema and Onyango (2021); Meigaru et al (2019); Meyers and VanGronigen (2019); Meyers and Hitt (2018); Mintrop and MacLellan (2002); Russell and Sharpe (2014); Strunk et al (2016); Waters and Marzano (2006) found that school academic excellence is achieved when the organizational strategic plan is implemented effectively. This is also supported by Bryson et al (2018); Wolf and Floyd (2017); Zakayo (2018) who explained that the organizational strategic plan influences and has a positive impact on school academic achievement.…”
Section: The Relationship Between the Implementation Of Organizationa...supporting
confidence: 68%